Influence Skills Development and Skill Effectiveness Factors on Youth Unemployment Mediated by Improved Work Readiness Competencies - Hartono, Hartono; Adinda Jennifer Pardede; Donny Melianto; Yoni Evan Pratama (Jurnal Multidisiplin Sahombu, 2025)
This type of research uses explanatory research, the research approach uses a quantitative approach. The research sample was 150 respondents. Objective of this study: 1) to analyze the influence of development skills to attract unemployment on youth. 2) to analyze the influence of effectiveness skills to attract unemployment on youth. 3) to analyze role mediation improvement competence readiness Work in connection between development skills and subtraction unemployment on youth. 40 to analyze role mediation improvement competence readiness Work in connection between effectiveness skills and subtraction unemployment on youth. The results showed that: 1) Development skills influence positively and significantly to subtraction unemployment on youth with mark original sample is 0.635. 2) Effectiveness skills Also had a significant influence on subtraction unemployment with the original sample value was 0.371. 3) Increase competence readiness Work plays a role as variable significant mediation in connection between development skills and subtraction unemployment with the original sample value is 0.441. 4) Increase competence readiness Work plays a role as variable significant mediation in connection between effectiveness skills and subtraction unemployment with the original sample value is 0.256